Manganese-Mediated Aerobic Oxidative Denitroalkylation of β-Nitrostyrenes with Alkylboronic Acids - Yu, Zi-yuan; Hu, Jing-jiang; Yu, Ya-xuan; Yuan, Yan-qin; Guo, Sheng-rong (Synlett, 2023)
An aerobic oxidative stereoselective denitroalkylation of β-nitrostyrenes under mild conditions by using an alkylboronic acid as the alkyl source was achieved. This protocol accepts a broad scope of β-nitrostyrenes and alkylboronic acids, leading to the formation of C(sp3)–C(sp2) bonds. Air was employed to reoxidize the resultant Mn(II) species back to Mn(III) during the catalytic cycle.
Keywords: manganese catalysis; denitroalkylation; alkylboronic acids; nitrostyrenes; radical reaction; aerobic oxidation